Multilevel analysis of the predictors of completion of the continuum of maternity care in Ethiopia; using the recent 2019 Ethiopia mini demographic and health survey - Gossa Fetene Abebe; Dereje Zeleke Belachew; Desalegn Girma; Alemseged Aydiko; Yilkal Negesse (BMC, 2022)
Abstract Background Despite the significant benefit of the continuum of care to avert maternal and neonatal mortality and morbidity, still the dropout from the continuum of care remains high and continued to become a challenge in Ethiopia. Therefore, this study aimed to assess the level of completion along the continuum of maternity care and its predictors among reproductive-age women in Ethiopia. Methods A secondary data analysis was done using the 2019 mini Ethiopian demographic health survey. A total weighted sample of 2,905 women aged 15-49 years who gave birth in the last five years preceding the survey and who had antenatal care visits was included. A multilevel mixed-effects logistic regression model was used to examine the predictors that affect the completion of the continuum of maternity care services. Finally, statistical significance was declared at a p-value < 0.05. Results In this study, the overall prevalence of completion along the continuum of maternity care was 12.9% (95%CI: 11.1 - 14.9%). Attending higher education (AOR = 2.03: 95%CI; 1.14 - 3.61), belonged to medium wealth status (AOR = 1.69: 95%CI; 1.07 - 2.66), belonged to rich wealth status (AOR = 2.05: 95%CI; 1.32, 3.17), and informed about danger signs during pregnancy (AOR = 2.23: 95%CI; 1.61, 3.10) were positively associated with the completion of the maternity continuum of care. However, late initiaton of first antenatal care visits (AOR = 0.66: 95%CI; 0.49, 0.89), being rural resident (AOR = 0.67: 95%CI; 0.42 - 0.93), lived in the Afar (AOR = 0.36: 95%CI; 0.12 - 0.83) and Gambella (AOR = 0.52: 95%CI; 0.19 - 0.95) regional states were negatively associated with the completion of the continuum of maternity care. Conclusion Despite most of the women using at least one of the maternity services, the level of completion along the continuum of care after antenatal care booking remains low in Ethiopia. Therefore, enhancing female education and economic transitions with special consideration given to rural, Afar, and Gambella regional state residents. Counseling towards the danger signs of pregnancy and its complications during antenatal care follow-upshould be strengthened. . Furthermore, the identified predictors should be considered when designing new policies or updating policies and strategies on maternity services uptake to step-up its full utilization, which in turn helps in the achievement of the sustainable development goals of ending preventable causes of maternal, neonatal, and child death by 2030.